Concentration Analysis of Türkiye’s Light Commercial Vehicle Sector: A Strategic Approach to Market Dominance - Yücel, Sevgi; Dilek, Serkan; Yücel, Mustafa (Sosyoekonomi, 2025)
Light commercial vehicles (LCVs) hold considerable potential to significantly influence various aspects of the economy, including trade, production, and services. This study examines the competition within Türkiye’s light commercial vehicle market from a strategic management perspective. The analysis reveals high concentration, indicating a limited competition landscape dominated by a few companies. The results suggest that firms must develop strategic flexibility to adapt to this concentrated environment. This study contributes to the literature by emphasising the need for adaptability and flexibility in maintaining competitiveness within Türkiye’s LCV sector.